Genetics and epigenetics in primary Sjögren's syndrome. (13th May 2021) - Imgenberg-Kreuz, Juliana; Rasmussen, Astrid; Sivils, Kathy; Nordmark, Gunnel
Abstract: Primary Sjögren's syndrome (pSS) is considered to be a multifactorial disease, where underlying genetic predisposition, epigenetic mechanisms and environmental factors contribute to disease development. In the last 5 years, the first genome-wide association studies in pSS have been completed. The strongest signal of association lies within the HLA genes, whereas the non- HLA genes IRF5 and STAT4 show consistent associations in multiple ethnicities but with a smaller effect size. The majority of the genetic risk variants are found at intergenic regions and their functional impact has in most cases not been elucidated. Epigenetic mechanisms such as DNA methylation, histone modifications and non-coding RNAs play a role in the pathogenesis of pSS by their modulating effects on gene expression and may constitute a dynamic link between the genome and phenotypic manifestations. This article reviews the hitherto published genetic studies and our current understanding of epigenetic mechanisms in pSS.